Results of the survey on studying finance basics - Baranyi Aranka; Csernák József; Tóth Eszter; Бороні А. (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola-"RIK-U" Kft., 2019)
Abstract. In our paper we wish to highlight whether there is a need to modify the teaching methodology used for teaching the discipline of finance basics and, if so, in what direction it is practical to start. Our objective is not to criticize the education system, but to enhance the complex way of thinking on the part of the students. We, the instructors in higher education, need to adapt our teaching techniques to this ever-changing, challenging situation while not forgetting the traditional teaching methods, but complementing them. We must make the most of the opportunities offered by modern technology for success. Nothing justifies the timeliness of our research more than the search for other forms and methods of effective financial knowledge transfer at other higher education institutions.

Tanulmányunkban arra kívánunk rávilágítani, hogy a pénzügyi ismeretek diszciplína elsajátítása során alkalmazott oktatási módszertant szükséges-e átalakítani, és ha igen, akkor azt milyen irányban célszerű megtenni. Ezzel nem az oktatási rendszer kritikáját kívánjuk megfogalmazni, hanem a hallgatók oldaláról tapasztalt komplex gondolkodás elősegítését erősíteni. Nekünk – a felsőoktatásban oktatóknak – ehhez a folyamatosan változó, kihívásokkal teli helyzethez kell az oktatási technikáinkat igazítani, ezzel nem elfeledve a régi oktatási módszereket, hanem azt kiegészítve, a siker érdekében a modern technika adta lehetőségeket maximálisan ki kell használnunk. Kutatásunk létjogosultságát mi sem bizonyítja jobban, minthogy más felsőoktatási intézményben is keresik a hatékony pénzügyi ismeretátadás oktatási formáit és módszereit.
https://kmf.uz.ua/wp-content/uploads/2021/02/limes-2019_tom-vi_vi-evfolyam.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00008405
Keywords: financial knowledge; empirical; teaching methods; teaching